Impact of error in criminal sin - منعم, فراس عبد الله; كاظم, حيدر لطيف (Journal of Legal Sciences, 2019)
The basis of criminalization hi the penal code is the protection of rights whether the rights are related to human life or its property or the rights related to the protection of public property any attack on these rights is a crime the crime does not take place unless there is a physical and moral corner  In addition the criminal intent of the offender must be available to the offender ie that he has knowledge of all the crimes  of the crime as one of the elements of the intention But what if the person was wrong during the commission of the act the elements of the crime or all of it does this affect the criminal intent of the perpetrator or not since the importance of organizing the provisions of error and the impact of it whether it is the element of mayors or error because the mistake of sin is it the heart of criminal liability came our research after the mistake of criminal sin from Necessity to distinguish between the effect of error on will and error and whether a person is guilty of committing the act without addressing the element of science and whether the blame that is directed to the person  is reflected in the psychological relationship between the materiality of the crime and the offender purely or that the blame not only the presence of the above relationship My evaluation of the active course requires the existence of the will to sin and therefore requires the availability of science has the possibility of blame